Monte Carlo Modeling of Photon Propagation Reveals Highly Scattering Coral Tissue - Wangpraseurt, Daniel; Jacques, Steven L.; Petrie, Tracy; Kühl, Michael (Frontiers in Plant Science, 2016)
Corals are very efficient at using solar radiation, with photosynthetic quantum efficiencies approaching theoretical limits. Here, we investigated potential mechanisms underlying such outstanding photosynthetic performance through extracting inherent optical properties of the living coral tissue and skeleton in a massive faviid coral. Using Monte Carlo simulations developed for medical tissue optics it is shown that for the investigated faviid coral, the coral tissue was a strongly light scattering matrix with a reduced scattering coefficient of μs’ = 10 cm-1 (at 636 nm). In contrast, the scattering coefficient of the coral skeleton was μs’ = 3.4 cm-1, which facilitated the efficient propagation of light to otherwise shaded coral tissue layers, thus supporting photosynthesis in lower tissues. Our study provides a quantification of coral tissue optical properties in a massive faviid coral and suggests a novel light harvesting strategy, where tissue and skeletal optics act in concert to optimize the illumination of the photosynthesizing algal symbionts embedded within the living coral tissue.